Inhibition of methylation and notch receptors in cutaneous melanoma - Oliveira , Daniel Arcuschin de; Junior , Cláudio Porta Fernandes; Machado , Paula Carolina Dias; Filho, Renato Santos de Oliveira (Seven Editora, 2023)
Cutaneous melanoma is skin cancer that originates from melanocytes or their precursors, melanoblasts and stem cells, being a cancer with high mortality. It is considered the most serious type of skin cancer because of its ability to spread quickly to other parts of the body (Shain 2016). Excessive exposure to ultraviolet radiation from the sun (a factor modifiable by human action) is its main external cause, with heredity predominating as the main cause in about 8 to 10% of cases. This includes prolonged exposure to the sun without adequate protection as well as the use of artificial tanning beds, which emit radiation similar to that of the sun. DOI:https://doi.org/10.56238/innovhealthknow-022